Determinants of tyrosylprotein sulfation coding and substrate specificity of tyrosylprotein sulfotransferases in metazoans. (25th November 2016) - Hartmann-Fatu, Cristina; Bayer, Peter
Abstract: This short review likes to give a historical view on the discovery of metazoan Tyrosylprotein Sulfotransferases (TPSTs) setting its focus on the determinants of substrate specificity of these enzymes and on the hitherto knowledge of the sulfation coding mechanism. Weak points of the to-date models of sulfation coding will be outlined and a more detailed and complex view on tyrosylprotein-sulfation coding will be presented with respect to recent cellular investigations on TPSTs. Graphical abstract: Highlights: Tyrosyl-sulfation is a functional important modification of many secreted proteins. Tyrosylprotein sulfotransferases (TPST) catalyze this post-translational modification. Human TPSTs are expressed in two isoforms which recognize different substrates. The determinants of substrate selection and sulfation coding are barely understood. Higher organization levels of TPSTs have recently been discovered in the trans -Golgi.